3x-5x-7=-2x+5-7

Simple and best practice solution for 3x-5x-7=-2x+5-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5x-7=-2x+5-7 equation:



3x-5x-7=-2x+5-7
We move all terms to the left:
3x-5x-7-(-2x+5-7)=0
We add all the numbers together, and all the variables
3x-5x-(-2x-2)-7=0
We add all the numbers together, and all the variables
-2x-(-2x-2)-7=0
We get rid of parentheses
-2x+2x+2-7=0
We add all the numbers together, and all the variables
-5!=0
There is no solution for this equation

See similar equations:

| 3=1/2y | | 25=-5+2/3m | | y+1116=4 | | 12x-24x=-36x | | 1.8x=1.5x+18.72 | | x/8-17=7 | | 12x-24x=36x | | .6x+9=7x-5 | | -3-1/4x=9 | | 3g=-7 | | 9y+3=180 | | 7x+2=-35 | | -0.54=00.4h | | -5x+2(-5x-10)=-50 | | 4y-2°=21° | | (–17––14)×(10+18÷–9)=a | | -2x-16=-5(x+5) | | 3x+18+4x+15=180° | | 9+3y=180 | | 9.76–5.15x+(–10.85x)=8.76–11 | | 51+3y=180 | | 3x+12=5x-60 | | a/30=14 | | 6(6x+5)=36x+30 | | |4x+12|+5=21 | | -6(x+3)=-8x-36 | | 3^5x=9^2 | | (3x−9)+(x+3)=180 | | 7x+9=5+15 | | 996(12+69)=12x+77 | | -22/3x=-4/7 | | a/a-7=32 |

Equations solver categories